Decentralized finance – How triple-entry accounting and distributed ledger technology is revolutionizing the world of financial services from a business perspective - Lennart T. Schuldt; Markus Peskes (ZBW – Leibniz Information Centre for Economics, 2023)
Decentralized finance (DeFi) is a rapidly growing science that leverages distributed ledger technology (DLT) to offer peer-to-peer financial services. The DeFi ecosystem consists of decentralized applications that range from traditional financial services like decentralized stock exchanges (DEX) and lending platforms to novel services like flash loans. By eliminating the need for intermediaries and leveraging the public design of DLT networks, DeFi offers a more efficient, transparent, and accessible financial system. This results in lower transaction costs, higher control for users, and increased accessibility. The interoperable nature of DeFi applications enables the creation of new applications and financial services through the use of existing applications, which leads to a high degree of comparability and flexibility, allowing network participants to efficiently execute services. However, there are also barriers to the wider adoption of DeFi, such as the unsettled regulation in many countries, and the current user experience, which requires technical expertise and is less user-friendly than traditional centralized financial services. The strong adoption of DeFi by individuals and surveys indicating growing interest in DeFi by businesses will likely lead to these barriers being overcome as the user base grows. Despite the volatility of the crypto market, the trend of increasing adoption of DeFi applications is evident and reflected in an increasing number of users, projects, market capitalization of projects, and total value locked. Thus, DeFi is creating a decentralized financial system in parallel with the traditional centralized system, depriving it of a growing amount of resources.
Keywords: G23; G2; M16; M21; 330; Finance; Decentralized Finance; Controlling; DeFi; triple-entry accounting; accounting; financial services; distributed ledger technology